Geogebra Application for Trigonometry Subject: A Quasi-Experimental Research - Rholey R. Picaza (East Asian Journal of Multidisciplinary Research, 2023)
This study aimed to investigate Geogebra representation as a strategy in improving students’ achievement in Trigonometry. This research employed an experimental design. The participants of this study were college students from Davao De Oro State College T-test was used to determine if there is a significant difference in the pre-test, post-test and gain scores in trigonometric functions of control and experimental groups. Results showed that there is a significant difference in the post-test and gain scores of the control and experimental groups. This means that students who were taught Trigonometric functions using Geogebra performed better than students who were taught using the traditional approach. This only shows that Geogebra is an effective strategy in teaching Trigonometry subject.